Treatment of aseptic non-union after intramedullary nailing without removal of the nail. (June 2017) - Garnavos, Christos
Abstract: Failure of bone healing after intramedullary nailing of a diaphyseal long bone fracture is a severe complication that requires an effective management to ensure the best chances for successful bone-union and termination of a long period of incapacity and morbidity for the sufferers. Traditional procedures require removal of the existing nail and re-fixation with wider nail, plate or external fixation constructs. The concept that bone union can be obtained with the existing nail in situ is gaining popularity as its removal adds trauma and potential complications and prolongs the operating time. This article reviews all techniques that have been proposed for the management of aseptic diaphyseal long bone non-unions that stimulate bone healing without removing the existing nail.